2018
DOI: 10.1002/brb3.941
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrant circulating miRNAs in Parkinson's disease plasma samples

Abstract: ObjectiveTo detect the aberrant expression of circulating miRNAs and explore the potential early diagnostic biomarkers in patients with Parkinson's disease (PD).MethodsPlasma samples were collected from 25 treatment‐naïve PD‐diagnosed patients and 25 healthy controls followed by a real‐time PCR‐based miRNA screening analysis of neuron disease‐related miRNAs.ResultsA subset of miRNAs with aberrant expression levels in the plasma of PD‐diagnosed patients were identified including upregulation of miR‐27a and down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 48 publications
1
61
0
1
Order By: Relevance
“…Abnormal miRNA expression has been linked to many human diseases, and miRNAs have been identified as diagnostic and prognostic biomarkers for several disorders, including PD 32,33,34,35,36 . However, no PD-specific miRNAs have been identified in the gut for the pre-clinical diagnosis of PD so far 37,38,39 . To address this, we studied functional and molecular changes in the ENS of A30P mice before onset of PD symptoms to identify gut-related biomarkers for early stages of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal miRNA expression has been linked to many human diseases, and miRNAs have been identified as diagnostic and prognostic biomarkers for several disorders, including PD 32,33,34,35,36 . However, no PD-specific miRNAs have been identified in the gut for the pre-clinical diagnosis of PD so far 37,38,39 . To address this, we studied functional and molecular changes in the ENS of A30P mice before onset of PD symptoms to identify gut-related biomarkers for early stages of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Although research into PD has been performed for nearly a century, there is still a large amount of work to be done exploring the pathogenesis of the disease. Accordingly, it is imperative to identify useful biomarkers for early diagnosis of PD, especially prior to the onset of motor symptoms [4]. Up to now, the current therapeutics for PD only alleviates the symptoms, and when the full-blown syndrome occurs, there is no disease-modifying way available to treat the disease.…”
mentioning
confidence: 99%
“…Chen et al [4] provided a set of novel miRNA candidates, including up-regulated miR-27a and downregulated let-7a, miR-142-3p, let-7f and miR-222, for detecting PD. Chen et al [4] provided a set of novel miRNA candidates, including up-regulated miR-27a and downregulated let-7a, miR-142-3p, let-7f and miR-222, for detecting PD.…”
mentioning
confidence: 99%
“…This finding suggests that cf-microRNAs might discriminate Parkinson's disease multisystem atrophy patients ( 62 ). Recently, Chen et al ( 63 ) suggested that plasma miR-27a might be a potential biomarker of therapeutic targets in Parkinson's disease.…”
Section: Cnas In the Plasma And Serum In Neurological Disordersmentioning
confidence: 99%